1109 PULMONARY PRESSUR TREND ANALYSIS IN PATIENTS UNDERGOING MITRACLIP. (15th December 2022) - Lecis, Dalgisio; Minasi, Vincenzo; Galluccio, Chiara; Idone, Gaetano; Marchei, Massimo; Di Landro, Alessio; Macrini, Massimiliano; Oro, Pietro; Manni, Giulia; Illuminato, Federica; Marsili, Giorgia; Muscoli, Saverio; et al.
Abstract: Mitral regurgitation (MR) is the second most frequent valve heart disease in Europe and its underlying mechanism primary-organic (due to disease of the mitral leaflets), or secondary-functional (where valve leaflets and chordae are structurally normal and MR results from alterations in left ventricle and left atrium geometry), determines the therapeutic approach. Transcatheter Edge-to-Edge Repair (TEER) with MitraClip implantation is a minimal-invasive treatment that according to 2021 ESC Guidelines should be considered (class of recomandation IIa) in selected symptomatic patients with severe MR despite optimal medical therapy, not eligible for surgery and fulfilling COAPT trial inclusion criteria, suggesting an increased chance of responding to treatment. Optimal valve morphology features for TEER are central pathology (second scallop), no leaflet calcifications, mitral valve area >4cm2, mobile length of posterior leaftel >10 mm, coaptation depth <11mm, normal leaflet strength and mobility, flail width <15 mm, flail gap <10 mm. TEER may be considered (class IIb) only in selected cases when the COAPT criteria are not fulfilled with the aim of improving symptoms and quality of life. MR occurs during systole, that at normal heart rates represents 30-50% of the cardiac cycle. As such, marked left atrial (LA) pressure elevation is present only transiently, representing less of a drive to development of secondary pulmonary hypertension compared to chronic LA pressure elevation seen in severe mitral stenosis. Anyway, in patients with severe MR echocardiography often reveals elevated systolic pulmonary artery pressure (PAPs) and MitraClip implantation usually is associated with a slight increase of the trans-mitral gradient with possible repercussions on pulmonary pressures. To better describe the effect of MitraClip implantation on pulmonary pressures and clinical outcomes we did a retrospective study enrolling in the period 2012-2022 thirty-six patients with severe mitral regurgitation treated with TEER. Compared to the last year presentation, we add eleven patients. The target was still to evaluate the clinical outcomes (symptoms, signs of heart failure, NYHA functional class) and the pulmonary pressures assessed by an echocardiographic examination before and after the intervention. At 6-month follow-up we observed in all patients with repaired mitral regurgitation an improvement in the NYHA class (from IV to II) without re-hospitalization. In addition we notice a more pronounced trend in the reduction of the mean sistolic pulmonary arterial pressure, estimated at around 2.86 mmHg ± 14 mmHg (p 0.24, 95% C.I. -7.69 to 1.94) with an unchanged left ventricle ejection fraction. Moreover, the echocardiographic exam showed a normalization of the S and D waves pattern in the pulmonary veins at the PW Doppler evaluation. These new data reinforced the idea that the clinical improvement and the reduction of dyspnea in these patients underwent TEER is related to a reduction of pressures in the pulmonary circulation regardless of the ejection fraction. This finding could be used as a tool that the cardiologist has to evaluate in the echocardiography lab to reveal a new mitral valve disfunction. Despite the addition of the new patients, the sample is still relatively small. However, considering the improvement of the results with the enlargement of the sample, the goal is to enroll additional patients to make the study even more meaningful.